Effects of Supplementation with Fermented of Total Mixed Ration (FTMR) Feed and Biochar on Growth Performance in Local “Yellow” Cattle - INTHAPANYA, Sangkhom; SIRIVONG, Buason; PHONGPHANITH, Sengsouly; CHANTHAKOUN , Vongpasith; NAOYENG, Khamkeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This study undertook an assessment of the potential benefits in term of supplementing the fermented total mixed ration (FTMR) feed and biochar on growth performance from local “Yellow” cattle fed Napier grass and straw as basal diets. Twelve local “Yellow” cattle with average of initial live weight 83.3 ±1.3kg were assigned in a completely randomized design (CRD), 03 treatments and with 04 replicates. The treatments were: CTL: no supplement; FTMR: fermented total mixed ration supplement and FTMR-BC: fermented total mixed ration and biochar supplement. The basal diet was Napier grass fed ad-libitum and straw fed at 0.5% of LW (DM basis). The fermented total mixed ration feed (FTMR) and biochar (BC) were added to the diet at the rate of 30% and 1.0% in the DM intake. The trial lasted 120 days following a 14days adaptation to the diets. The animals were weighed at the beginning of the study and then every 15days until the study was completed for measurement the live weight change. Feed offer and residue samples were collected from the animals in the morning before feeding, and every 15 days during the study for determine the feed intake. The results showed that total DM intake and intake per live weight change were different among the treatments (P<0.05). There was increased DM intake within treatment of FTMR-BC than FTMR and CTL treatment, respectively. However, the FTMR-BC treatment was increased 26.7% of DM intake when was compared with CTL treatment. The live weight change was trended to increase by periods of experiment, and was higher for treatment of FTMR-BC than treatments (FTMR and CTL), respectively. Supplementing on fermented total mixed ration with biochar by using ad-libitum of Napier grass and straw fed at 0.5% of LW (DM basis) were provides the joint potential of being a protein supplement for ruminants especially increasing feed intake and growth performance of local “Yellow” cattle and it’s readily accessible for smallholder producers through intensive cattle fattening.